2017
DOI: 10.1007/s10147-016-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

Histologic grade and peritoneal cytology as prognostic factors in type 1 endometrial cancer

Abstract: G2 histology and positive peritoneal cytology were independent prognostic factors for DFS and OS in type 1 endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The majority of newly diagnosed patients have a favorable prognosis with a 5-year survival rate of 81.8%, but patients with recurrent/metastatic disease have poor survival, with a 5-year survival rate of 55 and 42% after radiotherapy and chemotherapy, respectively (1,2). Clinical stage (7), histological subtype (8), grade (9), depth of invasive disease (10) and positive lymph node (11) have been reported as important prognostic factors. Elevated serum cancer antigen 125 level is observed during recurrence and tumor relapse (12).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of newly diagnosed patients have a favorable prognosis with a 5-year survival rate of 81.8%, but patients with recurrent/metastatic disease have poor survival, with a 5-year survival rate of 55 and 42% after radiotherapy and chemotherapy, respectively (1,2). Clinical stage (7), histological subtype (8), grade (9), depth of invasive disease (10) and positive lymph node (11) have been reported as important prognostic factors. Elevated serum cancer antigen 125 level is observed during recurrence and tumor relapse (12).…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, Tanaka et al have specifically analyzed 168 cases of endometrioid-type EC, and shown that the positive peritoneal cytology is an independent risk factor for OS and DFS. 17 In 2018, a multicenter retrospective study consisting of 1688 cases has shown that the positive peritoneal cytology is a high-risk factor for relapse, and the risk of recurrence in patients with positive peritoneal cytology is 3.07 times higher compared with the patients with negative peritoneal cytology. The author has recommended that peritoneal washing should be routinely performed.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…4 Although a limited number of articles have suggested that positive cytology is not an independent risk factor for adverse outcomes, [5][6][7][8][9][10] recent studies have repeatedly emphasized that positive peritoneal cytology is still associated with poor prognosis, even when other confounding factors are adjusted. [11][12][13][14][15][16][17][18][19][20] The prognostic value of peritoneal cytology in EC patients remains controversial. Therefore, we aimed to clarify whether positive peritoneal cytology was an independent risk factor in EC patients through a retrospective study in EC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Given that peritoneal cytology is not a part of surgical staging, the relationship between survival and peritoneal cytology particularly is still very controversial in early-stage patients. While some studies showed positive peritoneal cytology is related to high rates of recurrences and poor survival ( 7 , 10 , 11 ), some found out no relationship between positive peritoneal cytology and survival ( 28 , 29 ). Seagle et al ( 30 ) analyzed data from the National Cancer Database and reported that adjuvant CT provides better survival in patients who were diagnosed as an early endometrioid type of endometrial cancer patients with positive peritoneal cytology.…”
Section: Discussionmentioning
confidence: 99%